Training novice clinical psychologist trainees to implement effective CBT for anxiety disorders: training model and clinic outcomes. (12th December 2016) - O'Keeffe, Fiadhnait; Watson, Sue; Linke, Stuart
Abstract: The need for development of effective models of training and superivision for trainee clinical psychologists to build CBT competencies and to implement high-quality CBT is frequently highlighted. Effectiveness of trainee therapist outcomes working within different models of training, supervision and services is also important to establish. This paper reports on the development and outcome effectiveness of a model of training and supervision aimed at increasing CBT clinical skills and competence of trainee clinical psychologists offering CBT for anxiety disorders in an anxiety disorders clinic (ADC) in inner-city London. Details of the training and supervision model are provided, which was conducted over a period of 3 months, with ongoing weekly supervision throughout the intervention period. Pre- and post-intervention data were analysed from service users who attended the ADC over a 2-year period. Over the 2-year period, 10 trainees treated 57 clients. Data from completer and intention-to-treat samples indicated that scores on four outcome measures improved significantly: at post-therapy, 75% of service users who completed the intervention showed reliable and clinically significant recovery or improvement. When supported by appropriate training and supervision, as outlined in this training model, initially inexperienced trainee psychologists can achieve outcomes comparable to those obtained in other secondary-care settings with qualified therapists.